Relationship of Prostate-Urethral Angle and Intravesical Prostatic Prtusion with International Prostatic Symptoms Score and Uroflowmetry in Benign Prostatic Hyperplasia Patients - Tjahjodjati, Tjahjodjati; Santoso, Jumadi (International Journal of Integrated Health Sciences, 2015)
Objective: To investigate the correlation between Intravesical Prostatic Protrusion (IPP) and Prostate Uretral Angle (PUA) in Benign Prostatic Hyperplasia (BPH) patient with Lower Urinary Tract Symptoms (LUTS) on International Prostatic Symptoms Score (IPSS) and uroflowmetry.Methods: A cross sectional study was done to 71 BPH patients with LUTS who attended Urologic Clinic in Dr. Hasan Sadikin General Hospital and matched the inclusion and exclusion criterias. The Intravesical Prostatic Protrusion and PUA were measured using transrectal ultrasound and the degree of LUTS was measured using IPSS and uroflowmetry. Patients were classified based on PUA (<350 dan ≥350) and degree of IPP (grade 1< 5mm;II 5-10mm;III >10mm). Data were analyzed using Spearman correlation test. Results: Prostatic-Urethral Angle has a strong correlation with IPSS total and voiding (0.670 and 0.715) but the correlation was weak with IPPS storage (0.381). Furthermore, PUA has a strong negative correlation with Qmax dan Qave values. The bigger the PUA, the smaller Qmax dan Qave values. IPP has a strong correlation with IPSS total and voiding (0.645 and 0.662), but has moderate correlation with IPSS storage (0.442). Furthermore, IPP has no correlation with the values of Qmax, Qave, Voided volume and PVR.Conclusions: Prostatic-Urethral Angle and Intravesical Prostatic Protrusion have a strong correlation with the occurence of LUTS in BPH patients. Keywords: Benign prostatic hyperplasia, intravesical prostatic protrusion, lower urinary tract symptoms, prostate-urethral angle DOI: 10.15850/ijihs.v3n2.583